2001
DOI: 10.4049/jimmunol.167.4.1900
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Circumvents NF-κB Dependence in Retinal Pigment Epithelial Cells

Abstract: The human CMV (HCMV) is a persistent virus that may cause severe inflammatory responses especially in immunocompromised hosts. In different cell types, HCMV infection leads to the activation of the pleiotropic transcription factor, NF-κB, which triggers virus replication but also propagates cell-mediated inflammatory mechanisms that largely depend on PG synthesis. We investigated the interactions of HCMV and the NF-κB-dependent PG synthesis pathway in cultures of retinal pigment epithelial (RPE) cells that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 58 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…Phorbol esters have been reported to enhance active HCMV infection in acutely infected human umbilical vein endothelial cells (HUVEC) (55) and retinal pigmented epithelial (RPE) cells (13). Phorbol ester treatment of HUVEC prior to infection with the laboratory-adapted HCMV Ad169 strain, which is impaired in its ability to translocate to the HUVEC nucleus (54), increases the proportion of the cell population allowing active HCMV infection in a manner that is blocked by the PKC inhibitor staurosporin or RO-31-8220 (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phorbol esters have been reported to enhance active HCMV infection in acutely infected human umbilical vein endothelial cells (HUVEC) (55) and retinal pigmented epithelial (RPE) cells (13). Phorbol ester treatment of HUVEC prior to infection with the laboratory-adapted HCMV Ad169 strain, which is impaired in its ability to translocate to the HUVEC nucleus (54), increases the proportion of the cell population allowing active HCMV infection in a manner that is blocked by the PKC inhibitor staurosporin or RO-31-8220 (55).…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol ester treatment of HUVEC prior to infection with the laboratory-adapted HCMV Ad169 strain, which is impaired in its ability to translocate to the HUVEC nucleus (54), increases the proportion of the cell population allowing active HCMV infection in a manner that is blocked by the PKC inhibitor staurosporin or RO-31-8220 (55). The treatment of RPE cells with phorbol ester before or shortly after infection enhances HCMV activity via a PKC-dependent mitogen-activated protein kinase pathway, and this enhancement does not involve NF-B activity (13). Notably, MCMV replication in acutely infected murine fibroblasts is blocked by PKC inhibitors, which manifests as a decrease in the level of MIE gene expression (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further analyzed the contribution of the canonical, or classical, NF-B pathway by using dominant negative inhibitors of IB␣ and immortalized p65/RelA-deficient fibroblasts. Infection of fibroblasts by CMV has been shown to activate the translocation of transcriptionally active p50/p65 to the nucleus (10,19,27) and to induce activation of the p50 and p65 promoters by IE1 (19,54,55). Overexpression of HCMV IE1 has also recently been reported to induce transcription of the NF-B family member RelB (23).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that human CMV infection induces activation of NF-B (9,10,45,54), and the NF-B-responsive elements present in the MIEP (Fig. 1A) bind NF-B and are responsive to NF-B-mediated transcriptional enhancement in transient-transfection reporter-based expression assays (45).…”
Section: Vol 78 2004 Nf-b and CMV 745mentioning
confidence: 99%